The Gerasene Exorcism and Jesus' Eschatological Expulsion of Cosmic Powers Echoes of Second Temple Scapegoat Traditions in Mark 5.1-20 - Moscicke, Hans 1985- (2019)
In this article, I argue that ancient expulsion rites and early Jewish scapegoat traditions have influenced the composition of Mk 5.1-20. These rites and traditions inform Mark's portrayal of Jesus' transfer of the demons into the swine and their disposal into the sea, which heals the Gentile man. Jesus' scapegoat-like expulsion of Legion signals God's banishment of hostile spiritual powers from their positions of authority over the nations and augurs God's kingdom reign, in which Gentiles are released from bondage to cosmic forces, and their earthly counterparts, cleansed and welcomed into the family of God.
Keywords: Azazel; Jewish apocalypticism; Leviticus 16; the Gospel of Mark; Yom Kippur; elimination rituals; expulsion rituals; Scapegoat; the Book of Watchers; the Gerasene demoniac